Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction